Plan de exportación de panela orgánica pulverizada como endulzante hacia España (2021)
Colombia is characterized by being a country dedicated in a large part of its economy to agriculture, since it is a nation that thanks to its geographical location can dedicate 365 days a year to the production of agricultural products, in recent years the production of panela It has been suffering damages due to the low prices paid to peasant producers, for this reason the Colombian state has been granting incentives to the panela agro-industry, which has allowed the reactivation of farmers